INTEGRASI NILAI-NILAI BUDAYA LOKAL DALAM KEPEMIMPINAN KRISTEN: IMPLIKASINYA TERHADAP PENGEMBANGAN KOMPETENSI GURU DALAM PENDIDIKAN KRISTEN - Jelvi Greiza; Jelpin; Roslina Arungbua'; Merianti Datuan; Delfiyanti (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine the integration of local cultural values ​​into Christian leadership and its implications for teacher competency development in Christian education. Christian leadership is fundamentally oriented not only toward managerial aspects, but also toward the values ​​of service, love, and faith-based character building. In the context of Indonesia's culturally rich society, local cultural values ​​such as mutual cooperation, deliberation, respect for others, and social responsibility can be sources of wisdom that enrich leadership practices. This study uses a qualitative approach with a library study method that analyzes various scientific literature related to Christian leadership, local culture, and teacher competency. The results of the study indicate that the integration of local cultural values ​​into Christian leadership can create a more contextual, inclusive, and participatory educational environment. This condition has a positive impact on the development of teachers' pedagogical, professional, social, and personal competencies. Thus, leadership that integrates faith values ​​and local cultural wisdom can support the continuous improvement of teacher quality and the quality of Christian education.